Preclinical Toxicology Studies of Recombinant Human Platelet-Derived Growth Factor-BB Either Alone or in Combination with Beta-Tricalcium Phosphate and Type I Collagen. (21st December 2010) - Young, Conan S.; Bradica, Gino; Hart, Charlie E.; Karunanidhi, Anuradha; Street, Reva M.; Schutte, Lyndsey; Hollinger, Jeffrey O.
Abstract : Human platelet-derived growth factor-BB (hPDGF-BB) is a basic polypeptide growth factor released from platelets at the injury site. It is a multifunctional molecule that regulates DNA synthesis and cell division and induces biological effects that are implicated in tissue repair, atherosclerosis, inflammatory responses, and neoplastic diseases. This paper is an overview of the toxicology data generated from a broad testing platform to determine bone, soft tissue, and systemic responses following administration of rhPDGF-BB. Moreover, the systemic and local toxicity of recombinant human PDGF-BB (rhPDGF-BB) in combination with either beta-tricalcium phosphate ( β -TCP) or collagen combined with β -TCP was studied to determine dermal sensitization, irritation, intramuscular tissue responses, pyrogenicity, genotoxicity, and hemolytic properties. All data strongly suggest that rhPDGF-BB either alone or in combination with β -TCP or collagen with β -TCP is biocompatible and has neither systemic nor local toxicity, supporting its safe use in enhancing wound healing in patients.